Quantitative Determination of Azlocillin by Iodometric Method using Potassium Peroxomonosulfate - Karpova, Svitlana P. (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: Kinetics and stoichiometry S-oxidation reaction of sodium Azlocillin (Azl) by means of potassium hydrogenperoxomonosulfate in aqueous solutions using iodometric titration were studied. Materials and Methods: SecuropenÂ® - powder Azl sodium in flacons for preparation of solution for injections (Azl 1.0 g; 5.0 g) was used for analysis. A new iodometric method for quantitative determination of sodium Azl in SecuropenÂ® preparation using potassium hydrogenperoxomonosulfate (KHSO5) as analytical reagent was proposed. Peroxomonosulfate acid as triple potassium salt 2ÐšÐSO5âˆ™ÐšÐSO4âˆ™K2SO4 (OxoneÂ®) of â€œextra pureâ€ qualification was used as oxidant. Results: At pH 2â€“4 for 1 mole of penicillin, 1 mole of KHSO5 is consumed; the quantitative interaction is achieved within a time of more than 1 minute (observation time). The results were obtained by the recommended procedure for seven replicate titrations of mixtures containing the three species at various concentrations. Relative standard deviation = (0.8 âˆ’2.8) %, Î´ = (+0.2 â€¦âˆ’0.31) %. It can be seen that Azl can be determined successively with good accuracy and reproducibility. Conclusion: The new procedure was developed and ability of quantitative determination of penicillin in pharmaceutical preparation SecuropenÂ® by iodometric method using potassium hydrogenperoxomonosulfate (KHSO5) as analytical reagent was shown.